I Can Read ! The Fire Cat - Averill, Esther 1902-1992. (New York : HarperCollins, 1960)
When Pickles, a yellow cat with black spots, is rescued from a tree by firemen, he goes to live at the firehouse.
1
Keywords: Cats -- Juvenile fiction; Fire fighters -- Juvenile fiction; Fire departments -- Juvenile fiction; Cats -- Fiction; Fire fighters -- Fiction; Fire departments -- Fiction; Early readers